2001
DOI: 10.1016/s0924-9338(00)00533-2
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms as measured by the CDI in a population of northern Italian children

Abstract: The aim of this study was to evaluate some Children's Depression Inventory (CDI) psychometric properties and the prevalence of depressive symptoms in an unselected Italian sample of two hundred and eighty-four children aged 8 years. The CDI internal consistency was adequate (Cronbach's alpha:.80). The mean and standard deviation of CDI and the percentage of children at risk of depression (10.6%) in this sample are consistent with the figures reported by other studies carried out in northern Europe and North Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 34 publications
6
31
3
Order By: Relevance
“…The ratio of depression in the study is harmonious with the other studies (3,13,19). Toros et al (15) had found that depression prevalence in adolescents was higher in a coastal city in southern Turkey.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The ratio of depression in the study is harmonious with the other studies (3,13,19). Toros et al (15) had found that depression prevalence in adolescents was higher in a coastal city in southern Turkey.…”
Section: Discussionsupporting
confidence: 86%
“…Poverty was effective on depressive symptoms in children (Table 2). Poverty and dif- (5,13,24,37,38) showed that low economic status increases depression. It can be concluded that low economic status leads to depression via deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of depressive risk in the present sample was 4.2%, when the cutoff point of 19 suggested by Kovacs [30] was taken as threshold. This figure is much lower than those reported in other studies which concluded to prevalence rates around 10% using the same cutoff point of CDI score [17,28,36,43]. When the cutoff point of 13 was taken as threshold, the prevalence rate was somewhat higher (14.96%) than the prevalence figures of self-reported depressive morbidity obtained from studies in general population, but still much lower than those obtained from studies using the cutoff point of 13 of the CDI [17,43].…”
Section: Discussioncontrasting
confidence: 77%
“…This figure is much lower than those reported in other studies which concluded to prevalence rates around 10% using the same cutoff point of CDI score [17,28,36,43]. When the cutoff point of 13 was taken as threshold, the prevalence rate was somewhat higher (14.96%) than the prevalence figures of self-reported depressive morbidity obtained from studies in general population, but still much lower than those obtained from studies using the cutoff point of 13 of the CDI [17,43]. Since previous studies [10,24,27,48] indicate that CDI can be better used as a continuous measure of depressive symptoms [10] rather than as an accurate discriminatory (through cutoff scores) instrument for depression, further research using CDI along with other validated diagnostic measures for psychopathology in both clinical and nonclinical Greek populations (questionnaires and/or structured interviews) is needed.…”
Section: Discussioncontrasting
confidence: 77%